2010
DOI: 10.1371/journal.pone.0015541
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of Ing2 Results in Defective Spermatogenesis and Development of Soft-Tissue Sarcomas

Abstract: ING2 (inhibitor of growth family, member 2) is a member of the plant homeodomain (PHD)-containing ING family of putative tumor suppressors. As part of mSin3A-HDAC corepressor complexes, ING2 binds to tri-methylated lysine 4 of histone H3 (H3K4me3) to regulate chromatin modification and gene expression. ING2 also functionally interacts with the tumor suppressor protein p53 to regulate cellular senescence, apoptosis and DNA damage response in vitro, and is thus expected to modulate carcinogenesis and aging. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 66 publications
(97 reference statements)
2
62
0
Order By: Relevance
“…This study revealed the knockdown of ING2 may accelerate cell cycle progression, which provides evidence for the potential link between loss of ING2 and cancer development. Another report by Saito M provides an animal model to study idiopathic and iatrogenic infertility in men found the function of ING2 in spermatogenesis and also demonstrated an evidence of ING2 as a tumor suppressor by increased incidence of soft-tissue sarcomas in Ing2-/-mice [33]. Interestingly, a research on colon cancer suggest ING2 also play roles as a tumor oncogene, which demonstrated ING2 was upregulated and increased invasion by enhanced MMP-13 [22].…”
Section: Discussionmentioning
confidence: 94%
“…This study revealed the knockdown of ING2 may accelerate cell cycle progression, which provides evidence for the potential link between loss of ING2 and cancer development. Another report by Saito M provides an animal model to study idiopathic and iatrogenic infertility in men found the function of ING2 in spermatogenesis and also demonstrated an evidence of ING2 as a tumor suppressor by increased incidence of soft-tissue sarcomas in Ing2-/-mice [33]. Interestingly, a research on colon cancer suggest ING2 also play roles as a tumor oncogene, which demonstrated ING2 was upregulated and increased invasion by enhanced MMP-13 [22].…”
Section: Discussionmentioning
confidence: 94%
“…Apart from reduced size and higher incidence of lymphomas, Ing1 KO mice exhibit no other obvious morphological, physiological, or behavioral abnormalities, indicating that Ing1 function is dispensable for the viability under normal physiological conditions [14] and Ing2 might play a compensatory role in Ing1-depleted condition. In spite of high homology between ING1 and ING2, a different phenotype has been observed in their corresponding KO mice models [13][14][15]. Ing2 KO mice are characterized by defective spermatogenesis in males and higher incidence of soft tissue sarcomas [15].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of high homology between ING1 and ING2, a different phenotype has been observed in their corresponding KO mice models [13][14][15]. Ing2 KO mice are characterized by defective spermatogenesis in males and higher incidence of soft tissue sarcomas [15]. Interestingly, the major tumor type observed in Ing2 KO mice was histiocytic sarcoma which showed increased incidence preferentially in males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6G). Thus, the homologous down- (27). We therefore investigated the localization of MTA2 immunoexpression in testicular tissues of patients with impairment of spermatogenesis and in controls.…”
Section: Up-regulation Of Mta2 Expression By Fsh In Scs Is Mediated Vmentioning
confidence: 99%